Creative problem-solving techniques, paradigm shift and team performance. Issue 7 (6th October 2020) - Proctor, Tony
Abstract : Purpose: This paper aims to consider why creative problem-solving techniques may not always produce useful results and sets out to explain why this might be and what steps should be taken to avoid it happening. The paper provides an understanding of how different creative problem-solving techniques are best suited to gaining insights into problems requiring different degrees of paradigm shift. It argues that team members' personalities and thinking styles and team composition should be taken into account when using the techniques. It examines the role the facilitator plays in planning and conducting the ideation process. Design/methodology/approach: The paper provides simple illustrations of some of the creative problem-solving techniques. It reviews relevant literature and argues how individual differences of team members along with team composition can influence team performance in using the creative problem-solving techniques. Findings: Personality, thinking styles and learning styles are relevant to the effective use of creative problem-solving techniques. Team composition, team motivation and mood factors should also be taken into account. The facilitator is key in ensuring the efficacy of the problem-solving process. Originality/value: This paper will be helpful to academics who study creative problem-solving as well as informing management practitioners and trainers about the procedures and potential pitfalls to avoid.